1989
DOI: 10.1101/gad.3.7.1045
|View full text |Cite
|
Sign up to set email alerts
|

New suppressors of signal-sequence mutations, prlG, are linked tightly to the secE gene of Escherichia coli.

Abstract: Analysis of more than 100 extragenic suppressors of the lamB14D signal-sequence mutation {changes Val in the hydrophobic core region at position 14 to Asp) has revealed alterations that appear to lie at prlA (secYJ and secA {prlD), two loci known to be mutable to suppressor alleles, and a new suppressor termed priG. One allele of the new suppressor class, priG1, has been characterized in some detail. This suppressor counteracts, to some degree, the export defect conferred by a variety of signal-sequence mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…The expression of levansucrase in E. coli has limited the construction of some signal sequence Isolation of suppressor mutations for some of the E. coli signal sequence mutants has resulted in the identification of the various genes involved in the secretion machinery in E. coli. (1,5,25). We are currently isolating suppressor mutations of defective levansucrase signal peptides in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of levansucrase in E. coli has limited the construction of some signal sequence Isolation of suppressor mutations for some of the E. coli signal sequence mutants has resulted in the identification of the various genes involved in the secretion machinery in E. coli. (1,5,25). We are currently isolating suppressor mutations of defective levansucrase signal peptides in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…Signal sequence mutants of E. coli have aided both in understanding the role of signal sequences in the secretion process and in identifying E. coli genes involved in protein secretion (1,3,5,25). The mechanism of protein secretion in Bacillus subtilis has not been extensively studied, and few signal sequence mutants of B. subtilis have been reported (18,21).…”
mentioning
confidence: 99%
“…Since lamB14D causes a severe export defect, it is possible that the failure ofpriZI to suppress this mutation is a matter of degree rather than allele specificity, i.e., priZI is simply too weak. This degree of suppression is reminiscent of priGI, whose effect could be shown in a pulse-chase assay of the leaky lamB17D signal sequence mutation (24). Accordingly, we examined the ability of prlZl to increase the rate of signal sequence processing of LamB17D and found that the suppressor had no effect (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Strain construction by P1 transduction was performed as previously described (21). PD1 was constructed by using STA19R as the recipient and TST6 (malF::TnlO [24]) as the donor and selecting for tetracycline resistance. PD50C was one of the Dex+ and Xs revertants of STA19R.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation